Effects of germination inhibition on the dynamics of Quercus ilex stands - Li, Junqing; Romane, Francois J. (Journal of Vegetation Science, 1997)
Abstract. Germination of Quercus ilex L. in coppice stands of this species in the western Mediterranean Basin was examined and a germination inhibitory process is proposed to explain some germination traits. Germination rate and seedling biomass of Q. ilex were greatly modified by watering acorns with various concentrations of aqueous soil extracts from a Q. ilex coppice stand but also when the acorns were sown in soil from Q. ilex coppice stands. In the aqueous extract experiment, Q. ilex germination and seedling weight both decreased as the aqueous extract concentration increased. In the soil type experiment, Q. ilex soil decreased the Q. ilex germination rate. Comparative studies with Q. pubescens germination (this species, replaced by Q. ilex around 5 000 B.P., is assumed to form the climax vegetation of the region) revealed that Q. pubescens was less sensitive to the aqueous extracts and soils of Q. ilex coppice stands. Inhibition of Q. ilex seed germination could be a major reason for the poor seed regeneration and suggested a possible comeback of Q. pubescens.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Allelopathy; Mediterranean vegetation; Quercus pubescens Willd

Effects of germination inhibition on the dynamics of Quercus ilex stands - Li, Junqing; Romane, Francois J (Journal of Vegetation Science, 1997)
Abstract. Germination of Quercus ilex L. in coppice stands of this species in the western Mediterranean Basin was examined and a germination inhibitory process is proposed to explain some germination traits. Germination rate and seedling biomass of Q. ilex were greatly modified by watering acorns with various concentrations of aqueous soil extracts from a Q. ilex coppice stand but also when the acorns were sown in soil from Q. ilex coppice stands. In the aqueous extract experiment, Q. ilex germination and seedling weight both decreased as the aqueous extract concentration increased. In the soil type experiment, Q. ilex soil decreased the Q. ilex germination rate. Comparative studies with Q. pubescens germination (this species, replaced by Q. ilex around 5 000 B.P., is assumed to form the climax vegetation of the region) revealed that Q. pubescens was less sensitive to the aqueous extracts and soils of Q. ilex coppice stands. Inhibition of Q. ilex seed germination could be a major reason for the poor seed regeneration and suggested a possible comeback of Q. pubescens.
Keywords: Allelopathy; Mediterranean vegetation; Quercus pubescens Willd